Victim of Crime and the State’s Liability for the Result of Criminal Proceedings - Strada-Rozenberga, Kristīne; Gurevičs, Dāvids (Journal of the University of Latvia. Law, 2023)
This paper examines the issues related to the state’s liability for such a result of criminal proceedings that impairs the victim’s right to a fair trial. The views presented in this paper follow the notion of the victim’s constitutional rights in Latvia and the principles established in the jurisprudence of the European Court of Human Rights, particularly with respect to the victim’s right to an effective and thorough investigation of a crime. Consequently, this paper provides an analysis of Latvia’s regulative framework on reparation of harm caused by state’s unlawful actions in criminal proceedings and the implementation thereof in the case law.